A Pilot Study to Increase Fruit and Vegetable Intake in Pregnant Latina Women - Kimberly K. Trout PhD; Joanna McGrath MSN; Jill Flanagan MA; Marcia C. Costello PhD; Jesse C. Frey PhD (SAGE Publishing, 2012)
Previous studies have suggested that women have low dietary intake of fruits and vegetables. This study's objective was to test the effectiveness of a novel nutrition intervention (education about prenatal flavor learning) on increasing fruit and vegetable intake in a group of primarily Latina women at an urban prenatal clinic. Methods: The Harvard Service Food Frequency Questionnaire (HSFFQ) was administered to 2 groups at the same clinic at 2 time points for each group. The first group was a nonintervention, comparison group. The second (intervention) group received specific information about how a pregnant woman's food choices can influence subsequent solid food preferences of her infant, with encouragement given to increase fruit and vegetable choices. The HSFFQ was administered pre- and post-intervention for this group. Results: Combined fruit and vegetable intake declined from the administration of Q#1 to Q#2 in both the comparison (n = 28) and intervention (n = 31) groups. The decline was primarily the result of a decrease in vegetable intake, but it was not statistically significant. In the comparison group, only 23.3-36.6% of women were eating adequate daily servings of vegetables, and in the intervention group 32.3%-38.7%. In both the comparison and intervention groups, over 74% of the women were eating adequate daily servings of fruit at both time points. Conclusions: In this Latina population of pregnant women, there was no difference in fruit and vegetable intake after receiving education about prenatal flavor learning. These findings suggest that education alone may not be sufficient to change health behaviors.